2013
DOI: 10.4102/hsag.v18i1.663
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ experiences and understanding of workplace violence in a trauma and emergency department in South Africa

Abstract: Violence in South African society has reached epidemic levels and has permeated the walls of the workplace. The aim of the study was to gain a deeper understanding of how nurses experience and understand workplace violence perpetrated by patients, and to make recommendations to reduce this type of violence. A qualitative, exploratory and descriptive study was conducted to explore the experiences and coping mechanisms of nurses regarding workplace violence. The purposive sample comprised eight nurses working in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 18 publications
3
46
1
5
Order By: Relevance
“…[6][7][8] Studies showed that nurses are three times more likely to experience violence than any other professional group. 9 International Council of Nurses (ICN) claimed that globally more than two-thirds nurses did not feel safe at the workplace in 2004. Nearly 22% of nurses experienced frequent violence with patients and their relatives in European countries as well.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Studies showed that nurses are three times more likely to experience violence than any other professional group. 9 International Council of Nurses (ICN) claimed that globally more than two-thirds nurses did not feel safe at the workplace in 2004. Nearly 22% of nurses experienced frequent violence with patients and their relatives in European countries as well.…”
Section: Introductionmentioning
confidence: 99%
“…En total un 50% (n=3) dels articles posseeixen una qualitat metodològica alta i són inclosos en aquesta revisió (Hogarth, Beattie, y Morphet, 2016;Kennedy y Julie, 2013;Ramacciati, Ceccagnoli, y Addey, 2015), quedant excluits de la mateixa el 50% (n=3) restant (Angland, Dowling, y Casey, 2014;Tan, Lopez, y Cleary, 2015;Wolf y Delao, 2014). En la Taula 3 es presenten les idees claus de cadascun dels articles.…”
Section: Figura 1 Relació D'articles Escollits I Descartats Després unclassified
“…Les infermeres participants en un dels estudis referien sentir-se constantment en perill, amb una sensació de violència imminent (Kennedy & Julie, 2013). Aquesta percepció també es fa present als altres dos estudis analitzats, on les infermeres manifesten que la violència es una part ineludible de la seva feina, especialment la violència psicològica (Hogarth y col., 2016;Ramacciati et al, 2015).…”
Section: Discussió I Conclusionunclassified
See 2 more Smart Citations